Sistemas geoambientais prioritários para proteção, planejamento e gestão na planície costeira de Icapuí-CE - Silva, José de Arimatea da (2021)
The systemic analysis of the coastal plain, with the characterization of the interconnections between the morphogenetic, ecological and landscape components, provided the definition of priority environmental systems for the environmental conservation of the coastal plain of Icapuí, on the east coast of Ceará state. The matter and energy flows, and the socio-environmental components were specialized in order to guide actions of environmental protection, planning and management, with a focus on facing the effects of climate change observed along the coastal plain. The theoretical foundations were related to the geosystemic approach with definition of landscape components, derived from the connections of matter and energy fluxes provided by waves and tides, estuarine, wind, mass movements and aquifer dynamics. The other technical procedures resulted in thematic maps, which defined the spaces to be protected, in order to guarantee the maintenance of ecological services of provision and regulation and to provide local confrontations already characterized by climatic extremes. Thus, the integrated system for the protection of natural areas was systematized, with the definition of priority levels for management, with a focus on ecosystem services, biological diversity, landscape and socio-environmental aspects. The results were related to the territorial governance proposals, with the definition of priority areas systematized in the proposed macro-zoning. Ecological services defined with community representations will provide continuity of socio-environmental relationships, grouped for the recovery of environmental systems, in order to minimize coastal erosion, salinization of the free aquifer and loss of biodiversity. As a whole, the results provided an important database and proposals for territorial management, based on the definition of priority areas and identification of threats and weaknesses, in order to enhance the creation and expansion of protected areas in the municipality of Icapuí.